Continuing English language teacher education - a challenge?: uma entrevista com Vanderlei José Zacchi - Ana Antônia de Assis-Peterson (Universidade do Estado de Mato Grosso, 2014)
Vanderlei J. Zacchi is a Doctor in Linguistic Studies and English Literature from the University of Sao Paulo and is a professor of the Department of Letters in Foreign Languages and of the Graduate Program of Letters at the Federal University of Sergipe.  He is an adjunct researcher at the Centre for Globalization and Cultural Studies of the University of Manitoba, Canada and vice-coordinator of GT Transculturality, Language and Education of ANPOLL. His areas of interest are English as hegemonic language, teacher education, new literacies and culture and identity. He has published in both national and international journals. Ana Antônia de Assis-Peterson